An inorganic sulfide solid electrolyte and its preparation method and application

By introducing heterovalent ions such as Na and Sn, Si, Al, Ge into the inorganic sulfide solid electrolyte, the solid-solvent phase sulfide electrolyte is formed, which solves the problem of insufficient electrolyte performance in all-solid lithium batteries and achieves high ion conduction and excellent mechanical properties improve the cycle stability of the battery.

CN117117300BActive Publication Date: 2024-12-17GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311024709.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2024-12-17
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

The performance of existing inorganic sulfide solid electrolytes in all-solid lithium batteries is difficult to satisfy. They lack high ion conductivity, low Young's modulus and high elastic strain limits, resulting in volume changes in the battery during circulation, resulting in increased interface cracks and impedance.

Method used

By introducing Na element and heterovalent ions such as Sn, Si, Al, Ge into the inorganic sulfide solid electrolyte, a solid-solvent phase sulfide electrolyte is formed, and its chemical structure is adjusted to broaden the Li ion transport channel and reduce Young's modulus. And through an inert atmosphere-protected grinding and heat treatment process, an electrolyte with high ionic conductivity and excellent mechanical properties was prepared.

Benefits of technology

Inorganic sulfide electrolyte with high ion conductivity and low Young's modulus is achieved, which significantly improves the cycling performance and mechanical stability of all-solid lithium batteries, and reduces the damage to the electrodes by the volume changes during the charging and discharging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117117300B_ABST
    Figure CN117117300B_ABST
Patent Text Reader

Abstract

The present invention provides an inorganic sulfide solid electrolyte and a preparation method and application thereof. The inorganic sulfide solid electrolyte has a composition as shown in formula (I): Li 7+k‑i‑n Na i P j M k S l O m X n (I). The present invention obtains various types of sulfide solid electrolytes with solid solution phase structures by adjusting the ratio of Na, M (Sn, Si, Al, Ge) and O. The obtained inorganic sulfide solid electrolyte material has higher ionic conductivity and better mechanical properties, which can further realize the use of sulfide solid electrolyte materials in all-solid-state batteries and improve the cycle performance of sulfide all-solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an inorganic sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion secondary batteries play an extremely important role in modern society, especially the development of new energy vehicles and large-scale energy storage, which has pushed them to unprecedented heights. With the continuous improvement of the energy density and safety requirements of power batteries, the existing liquid lithium-ion battery system has approached the upper limit of energy density, and the flammable organic electrolyte makes the safety hazards of high-energy liquid lithium-ion batteries more prominent. All-solid-state batteries that use non-flammable inorganic solid materials as electrolytes can not only eliminate the safety hazards caused by organic electrolyte leakage and thermal runaway inside the battery during use, but also can be used under extreme conditions such as high and low temperatures. Solid electrolytes are the most critical materials in all-solid-state batteries. The development of inorganic solid electrolytes with high stability and high lithium ion conductivity is the key to the development of high-performance all-solid-state batteries.

[0003] Among many solid electrolyte materials, sulfide solid electrolytes are currently the most studied and have the greatest application potential. The main reason is that sulfide electrolytes have ion conductivity comparable to that of liquid electrolytes. For example, Li 10 GeP2S 12 Materials (room temperature ion conductivity 12mS / cm, Nature materials, 2011, 10(9):682) and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 (Room temperature ion conductivity 25 mS / cm, Nature Energy, 2016, 1(4): 16030.) Materials.

[0004] All-solid-state lithium batteries are almost incompressible, and the volume change of active materials during the cycle leads to a reduction in solid-solid contact points, cracks at the interface, and increased interface impedance. This requires that solid electrolyte materials should have good mechanical properties in addition to high ion conductivity, which usually requires electrolyte materials to have a smaller Young's modulus and a higher elastic strain limit to adapt to the volume changes of active materials and electrodes.

[0005] However, in the inorganic sulfide solid electrolytes reported so far, there is generally no attention paid to this, resulting in unsatisfactory performance of all-solid-state batteries. Chinese patents CN112563565A and CN115693032A respectively report a sodium-lithium composite solid electrolyte. The ion conductivity reported in CN112563565A is relatively low (0.81mS / cm), and the higher Young's modulus of the oxide is relatively high, which is not conducive to the performance of all-solid-state batteries. The same oxide electrolyte reported in CN115693032A, and its essence is a diaphragm for liquid batteries. The use of the intermediate organic layer will inevitably reduce the ionic conductivity of the material, and the use of organic matter is not conducive to the improvement of the safety performance of all-solid-state batteries. Chinese patent CN115189014A reports an inorganic sulfide-organic composite solid electrolyte, but the organic electrolyte with lower ionic conductivity reduces the ionic conductivity of the sulfide electrolyte, and the organic electrolyte preparation process is complicated, there is a risk of organic solvent contamination, and the organic electrolyte has poor thermal stability, which is not conducive to the improvement of the safety performance of solid-state batteries. None of the above reports involve the improvement of the mechanical properties of the electrolyte itself.

[0006] Therefore, it is necessary to develop an inorganic sulfide electrolyte material with high ion conductivity, low Young's modulus and high elastic strain limit to meet the practical use requirements of all-solid-state batteries. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides an inorganic sulfide solid electrolyte and a preparation method and application thereof. The inorganic sulfide solid electrolyte has high ion conductivity, low Young's modulus and high elastic strain limit.

[0008] In a first aspect, the present invention provides an inorganic sulfide solid electrolyte, the composition of which is shown in formula (I):

[0009] Li 7+k-i-n Na i P j M k S l O m X n (I);

[0010] Wherein, M is one or more of Sn, Si, Al, Ge, X is one or more of F, Cl, Br, I, 0.0 <i≤7.0,0.0<k≤0.3,0.7≤j+k≤1.0,3.0<l≤6.5,0.0<m<2.0,4.0≤l+m≤6.5,0.0≤n<1.8。

[0011] The present invention has found that when a small amount of Na element is added thereto, since the radius of Na ions is larger, it can play the role of a pillar in the Li ion transmission path, broaden the Li ion transmission channel, increase the Li ion transmission speed, and improve the ionic conductivity of the target electrolyte material. The introduction of one or more heterovalent ions in Sn, Si, Al, and Ge, and their coupling with Na ions can change the deformation of the stable PS4 standard tetrahedron in the sulfide solid electrolyte to form a non-standard tetrahedron, that is, each atom in the solid electrolyte can be displaced in a larger range, and the macroscopic manifestation is a reduction in the Young's modulus of the electrolyte material. At the same time, one or more heterovalent ions in Sn, Si, Al, and Ge are coupled with O negative ions, which enhances the stability of free S in the sulfide electrolyte, that is, improves the elastic strain limit of the sulfide solid electrolyte material.

[0012] In some preferred embodiments of the present invention, in the chemical formula of the inorganic sulfide solid electrolyte, 0.0 <i≤7.0,0.0<k≤0.15,0.8≤j+k≤1.0,4.5<l≤6.0,0.0<m<1.0,4.5≤l+m≤6.3,5.0≤l+n≤6.5,0.0≤n<1.8。

[0013] Further preferably, 2.5≤k+j+li≤7.0.

[0014] The optimized combination of the above parameters can further enhance the above effects and further improve the ion conductivity and mechanical properties of the electrolyte material.

[0015] The inorganic sulfide solid electrolyte provided by the present invention is a solid solution phase type sulfide solid electrolyte material.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned inorganic sulfide solid electrolyte.

[0017] The preparation method provided by the present invention comprises the following steps:

[0018] Under the protection of an inert atmosphere, the required raw materials are mixed according to the proportion and then ground;

[0019] The ground material is heat treated under the protection of an inert atmosphere.

[0020] In some specific embodiments of the present invention, the required raw materials are Li2S, Na2S, P2S5, MS2, LiCl and Li2O.

[0021] Furthermore, the grinding is carried out in a ball mill, the grinding linear speed v is 7.5-16.0 m / s, the grinding time t is 3-24 h, and 5.5E+05m≤v×t≤7.0E+05m.

[0022] Furthermore, the heat treatment is performed at a temperature of 400-600°C and for a time of 3-48 hours.

[0023] Further preferably, when M is Sn or Ge, the grinding conditions satisfy 5.5E+05m≤v×t≤6.5E+05m, the heat treatment temperature is 500-600°C, and the heat treatment time is 5-12h;

[0024] When M is Si or Al, the grinding conditions satisfy 6.3E+05m≤v×t≤7.0E+05m, the heat treatment temperature is 400-550°C, and the heat treatment time is 5-24h.

[0025] The inert atmosphere of the present invention refers to a gas atmosphere that does not participate in the reaction, and common inert gases include nitrogen, argon and the like.

[0026] The purpose of this grinding process is to give the raw materials enough energy to break them into a suitable particle size range, so that the raw materials can be mixed evenly under the grinding conditions, and some of the raw materials undergo glass transition. In the subsequent heat treatment process, they are further crystallized to form a material with a stable structure and a single crystal form.

[0027] The present invention has found that the preparation method of the inorganic sulfide solid electrolyte has an important influence on the final performance of the material. Within the above method, especially within the range of ball milling process parameters, the prepared material can have higher ion conductivity and lower Young's modulus. If it is not processed under the above conditions, the performance of the material cannot be guaranteed.

[0028] In some preferred embodiments of the present invention, M is Sn or Ge, 5.5E+05m≤v×t≤6.5E+05m, the heat treatment temperature is 500-600°C, and the heat treatment time is 5-12h.

[0029] In some preferred embodiments of the present invention, M is Si or Al, 6.3E+05m≤v×t≤7.0E+05m, the heat treatment temperature is 400-550°C, and the heat treatment time is 5-24h.

[0030] In a third aspect, the present invention also provides a use of any of the above-mentioned inorganic sulfide solid electrolyte materials in the preparation of an all-solid-state lithium secondary battery.

[0031] Specifically, the present invention provides a solid electrolyte layer, which includes the above-mentioned inorganic sulfide solid electrolyte or the inorganic sulfide solid electrolyte prepared by the above-mentioned preparation method.

[0032] The term "comprising" is an open description, that is, in addition to the inorganic sulfide solid electrolyte provided by the present invention, the solid electrolyte layer may also include other materials that can be used as solid electrolytes, or other components that will not substantially affect the inorganic sulfide solid electrolyte.

[0033] The present invention also provides an all-solid-state lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and the above-mentioned solid electrolyte layer.

[0034] Wherein, the negative electrode layer is a carbon negative electrode or a non-carbon negative electrode, preferably a silicon-based negative electrode or a lithium metal negative electrode, and more preferably a lithium metal negative electrode.

[0035] The present invention provides an inorganic sulfide solid electrolyte and a preparation method and application thereof. By adjusting the ratio of Na, M (Sn, Si, Al, Ge) and O, various types of sulfide solid electrolytes with solid solution phase structures are obtained. The obtained inorganic sulfide solid electrolyte material has higher ionic conductivity and more excellent mechanical properties, which can further realize the use of sulfide solid electrolyte materials in all-solid-state batteries and improve the cycle performance of sulfide all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is an X-ray diffraction pattern of the solid electrolyte material obtained in Example 4;

[0037] Figure 2 This is a SEM image of an electrolyte layer prepared with the solid electrolyte material obtained in Example 4 after 50 cycles of the all-solid-state battery;

[0038] Figure 3 This is a SEM image of an electrolyte layer prepared with the solid electrolyte material obtained in Comparative Example 2 after 50 cycles of the all-solid-state battery;

[0039] Figure 4 The cycle curves of the electrolyte materials obtained in Comparative Example 2, Example 4, Example 7, and Example 10 when applied to all-solid-state batteries. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0042] Examples 1-13

[0043] Examples 1-13 respectively provide an inorganic sulfide solid electrolyte, the composition of which is shown in Table 1, and the preparation method thereof is as follows:

[0044] In the glove box, follow the Li 7+k-i-n Na i P j M k S l O m X n Weigh Li2S, Na2S, P2S5, MS2, LiCl, and Li2O, place the above raw materials in a 50ml zirconium oxide ball mill, and add 50g of 5mm diameter zirconium oxide balls. Place the sealed ball mill on the ball mill and set the speed for ball milling. Collect the ball milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise. After sintering, the temperature naturally drops to 50°C to obtain Li 7+k-i-n Na i P j M k S l O m X n Solid electrolyte material (the linear speed, grinding time and sintering temperature are shown in Table 1).

[0045] The ionic conductivity and mechanical properties (Young's modulus and Poisson's ratio) of the obtained solid electrolyte material were tested, and the results are shown in Table 1.

[0046] Among them, the ionic conductivity was detected using electrochemical impedance spectroscopy.

[0047] Young's modulus is a physical quantity that describes the ability of a solid material to resist deformation, and the present invention uses an atomic force microscope nanoindentation method for detection.

[0048] Poisson's ratio refers to the ratio of the transverse normal strain to the axial normal strain when the material is subjected to unidirectional tension or compression, also called the transverse deformation coefficient, which is an elastic constant reflecting the transverse deformation of the material. The present invention uses the moiré interferometry method for detection.

[0049] Comparative Examples 1-13

[0050] Comparative Examples 1-13 respectively provide a solid electrolyte, whose composition is shown in Table 1. The preparation method refers to the embodiment, and the raw materials are adjusted accordingly. For example, in Comparative Example 2, the composition is Li6PS5Cl, and the raw materials weighed are Li2S, P2S5, and LiCl.

[0051] The same method as above was used to test the ion conductivity and mechanical properties (Young's modulus and Poisson's ratio) of the solid electrolyte material obtained in the comparative example. The results are shown in Table 1.

[0052] Table 1

[0053]

[0054] Figure 1 This is the X-ray diffraction diagram of the solid electrolyte material obtained in Example 4. It can be seen that the diffraction peak of the solid electrolyte material is sharp, indicating that its crystallinity is high.

[0055] It can be seen from the above results that the inorganic sulfide electrolyte material provided by the present invention has high ion conductivity and excellent mechanical properties, which are specifically manifested in low Young's modulus and high Poisson's ratio.

[0056] Application example: electrolyte materials in all-solid-state Li-LiNi 0.6 Co 0.2 Mn 0.2 Application of O2 secondary batteries

[0057] The electrolyte materials obtained in Comparative Example 2, Example 4, Example 7 and Example 10 are respectively applied to all-solid-state Li-LiNi 0.6 Co 0.2 Mn 0.2 O2 secondary battery.

[0058] The LiNi used 0.6 Co 0.2 Mn 0.2 The O2 positive electrode material is first coated with LiNbO2 on the surface using the sol-gel method, and the coating thickness is about 10nm. 0.6 Co 0.2 Mn 0.2 The ratio of O2-coated positive electrode material: electrolyte material: acetylene carbon = 60:30:10 (mass ratio) was weighed, and the three materials were ground in a mortar in a glove box for 20 minutes to mix them evenly. The above mixture was used as the positive electrode powder, the metal In sheet was used as the negative electrode, and the electrolyte material obtained in Comparative Example 2, Example 4, Example 7, and Example 10 was used as the electrolyte layer to assemble the all-solid-state Li-LiNi 0.6 Co 0.2 Mn 0.2 O2 secondary battery. The battery uses 0.1mA / cm 2 The current density was used for cyclic charge and discharge test.

[0059] Figure 2 The electrolyte layer prepared with the solid electrolyte material obtained in Example 4 has a SEM image after 50 cycles of the all-solid-state battery, which shows that it is flat, uniform and has no cracks, indicating that the electrolyte material with improved mechanical properties can significantly alleviate the damage to the solid electrode caused by volume changes during the charge and discharge process.

[0060] Figure 3The electrolyte layer prepared with the solid electrolyte material obtained in Comparative Example 2 has obvious cracks in the SEM image after the all-solid-state battery has been cycled for 50 weeks, indicating that the electrolyte material without mechanical property improvement has broken during the charge and discharge process.

[0061] Figure 4 The cycle curves of the electrolyte materials obtained in Comparative Example 2, Example 4, Example 7, and Example 10 when applied to all-solid-state batteries show that, compared with Comparative Example 2, the cycle stability of Example 4, Example 7, and Example 10 is greatly improved.

[0062] In summary, the inorganic sulfide solid electrolyte provided by the present invention has a simple composition, readily available raw materials, a simple preparation method, a low production cost, high lithium ion conductivity and excellent mechanical properties, and is expected to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An inorganic sulfide solid electrolyte, characterized in that: Its composition is shown in formula (I): Li 7+k-i-n So i Q j M k S l O m X n (I); Wherein, M is one or more of Sn, Si, Al, Ge, X is one or more of F, Cl, Br, I, 0.0 <i≤7.0,0.0<k≤0.3,0.7≤j+k≤1.0,3.0<l≤6.5,0.0<m<2.0,4.0≤l+m≤6.5,0.0≤n<1.8 The inorganic sulfide solid electrolyte has high ion conductivity, low Young's modulus and high elastic strain limit.

2. The inorganic sulfide solid electrolyte according to claim 1, characterized in that 0.0 <i≤7.0,0.0<k≤0.15,0.8≤j+k≤1.0,4.5<l≤6.0,0.0<m<1.0,4.5≤l+m≤6.3,5.0≤l+n≤6.5,0.0<n<1.8。 3. The inorganic sulfide solid electrolyte according to claim 1 or 2, characterized in that: 2.5≤k+j+li≤7.

0.

4. The method for preparing the inorganic sulfide solid electrolyte according to any one of claims 1 or 2, characterized in that: include: The required raw materials are mixed according to a proportion and then ground under the protection of an inert atmosphere; the ground materials are heat treated under the protection of an inert atmosphere.

5. The method for preparing an inorganic sulfide solid electrolyte according to claim 4, characterized in that: The grinding is carried out in a ball mill, the grinding linear speed v is 7.5-16.0 m / s, the grinding time t is 3-24 h, and 5.5E+05m≤v×t≤7.0E+05m.

6. The method for preparing an inorganic sulfide solid electrolyte according to claim 4, characterized in that: The heat treatment temperature is 400-600° C. and the time is 3-48 hours.

7. The method for preparing an inorganic sulfide solid electrolyte according to claim 6, characterized in that: M is Sn or Ge, 5.5E+05m≤v×t≤6.5E+05m, the heat treatment temperature is 500-600℃, and the heat treatment time is 5-12h; M is Si or Al, 6.3E+05m≤v×t≤7.0E+05m, the heat treatment temperature is 400-550°C, and the heat treatment time is 5-24h.

8. A solid electrolyte layer, characterized in that: The inorganic sulfide solid electrolyte comprises the inorganic sulfide solid electrolyte according to any one of claims 1 to 3 or the inorganic sulfide solid electrolyte prepared by the preparation method according to any one of claims 4 to 7.

9. An all-solid-state lithium secondary battery, characterized in that: It comprises a positive electrode layer, a negative electrode layer and the solid electrolyte layer according to claim 8.

10. The all-solid-state lithium secondary battery according to claim 9, characterized in that: The negative electrode layer is a carbon negative electrode or a non-carbon negative electrode.

11. The all-solid-state lithium secondary battery according to any one of claims 9 or 10, characterized in that: The negative electrode layer is a silicon-based negative electrode or a lithium metal negative electrode.

12. The all-solid-state lithium secondary battery according to claim 11, characterized in that: The negative electrode layer is a lithium metal negative electrode.